(Diisopinocampheyl)borane-Mediated Reductive Aldol Reactions of Acrylate Esters: Enantioselective Synthesis of Anti-Aldols - Allais, Christophe (2013)
[Image: see text] The (diisopinocampheyl)borane promoted reductive aldol reaction of acrylate esters 4 is described. Isomerization of the kinetically formed Z(O)-enolborinate 5Z to the thermodynamic E(O)-enolborinate 5E via 1,3-boratropic shifts, followed by treatment with representative achiral aldehydes, leads to anti-α-methyl-β-hydroxy esters 9 or 10 with excellent diastereo- (up to ≥20:1 dr) and enantioselectivity (up to 87% ee). Results of double asymmetric reactions of 5E with several chiral aldehydes are also presented.